Nasal respiratory function in children with bronchial asthma and obesity - R. N. Khramova; E. V. Tush; T. I. Eliseeva; V. A. Bulgakova; I. I. Balabolkin (Аллергология и Иммунология в Педиатрии, 2023)
.